2003
DOI: 10.1016/s0022-1996(02)00022-3
|View full text |Cite
|
Sign up to set email alerts
|

Job creation, job destruction, and the real exchange rate

Abstract: This paper contributes to an understanding of internationally generated adjustment costs by demonstrating a statistically significant and economically relevant effect of the real exchange rate on job creation and job destruction in U.S. manufacturing industries over the period 1973 to 1993. The responsiveness of these gross job flows to the real exchange rate reflects pervasive heterogeneity with respect to international conditions across firms, even within narrowly defined industries. We document this heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
92
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 20 publications
6
92
2
6
Order By: Relevance
“…This result is robust to using different measures of job flows, and is stable across a number of different estimations. Such evidence of a job destruction-driven adjustment is in line with earlier findings by Klein et al (2003a) for the US, and differs from what has been found for other European countries, in particular France (Gourinchas 1999) and Germany (Moser et al 2010), where the adjustment to RER shocks was mainly driven by the job creation margin. Moser et al (2010) attributed the difference between the US and Germany to the far-stricter employment protection legislation in Germany, which makes firing costly and thus prevents smooth adjustments to shocks through job destruction.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…This result is robust to using different measures of job flows, and is stable across a number of different estimations. Such evidence of a job destruction-driven adjustment is in line with earlier findings by Klein et al (2003a) for the US, and differs from what has been found for other European countries, in particular France (Gourinchas 1999) and Germany (Moser et al 2010), where the adjustment to RER shocks was mainly driven by the job creation margin. Moser et al (2010) attributed the difference between the US and Germany to the far-stricter employment protection legislation in Germany, which makes firing costly and thus prevents smooth adjustments to shocks through job destruction.…”
supporting
confidence: 75%
“…As previously mentioned, this paper builds upon previous work by Gourinchas (1988Gourinchas ( , 1999, Klein et al (2003a) and Moser et al (2010). More generally, it is related to the growing body of literature on the connections between international trade and the labor market, as reviewed by Klein et al (2003b) and Crino' (2009).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…However, studies that consider exchange rate effects beyond trade exposure, such as Gourinchas (1999) or Klein, Schuh and Triest (2003), do find systematic effects on employment flows. Klein et al (2003) find for the U.S. that job destruction, churning and net employment growth respond to exchange rate movements, while job creation is unresponsive. In the Brazilian case, Ribeiro, Corseuil, Santos, Furtado, Amorim, Servo and Souza (2004) compute industry-level rates of job creation and destruction to find that greater openness reduces employment through increased job destruction, with no effects on job creation, and that exchange rate depreciation increases job creation with no effect on job destruction.…”
Section: Introductionmentioning
confidence: 99%